Pendampingan BUMDes Asung Daya Kabupaten Semarang untuk Peningkatan Pengendalian Internal Siklus Pengeluaran - Ika Kristianti; Elika Cuntita Bella Deyena Tiwa; Gabriella Stefany; Stefi Febrianti; Lea Ayu Trihastuti; Aloysius Denis Erwin; Ezra Putri Yufiani Nafara (Universitas Kristen Satya Wacana Salatiga, 2020)
The main problem at BUMDes Asung Daya is the control weaknesses that results in the difficulty of mitigating existing risks, particularly related to the cash disbursement cycle. While on the other hand Asung Daya Village Social Enterprise were asked to stay afloat during the Covid-19 pandemic. The purpose of this activity is to assist Asung Daya Village Social Enterprise in creating better cash management by promoting optimal internal control. The method used in this activity is assistance, observation and case discussion. The result is the mapping of threats in the cash disbursement cycle, the formulation of preventive controls, the detection and improvement of each of its business activities, and the creation of a flowchart as part of the technical documentation of the Asung Daya Village Social Enterprise cash disbursement system.